Role of MicroRNA, LncRNA, and Exosomes in the Progression of Osteoarthritis: A Review of Recent Literature - Fang Xie; Yong‐li Liu; Xiu‐yuan Chen; Qian Li; Jia Zhong; Bin‐yu Dai; Xian‐fang Shao; Guan‐bao Wu (Orthopaedic Surgery, 2020)
Osteoarthritis (OA) is a common clinical degenerative disease characterized by the destruction of articular cartilage, which has an increasing impact on people's lives and social economy. The pathogenesis of OA is complex and unclear, and there is no effective way to block its progress. The study of the pathogenesis of OA is the prerequisite for the early diagnosis and effective treatment of OA. To define the pathogenesis of OA, this review considers the pathological mechanism of OA that involves microRNA, lncRNA, and exosomes. More and more evidence shows that microRNA, lncRNA, and exosomes are closely related to OA. MicroRNA inhibits the target gene by binding to the 3′‐ untranslated region of the targets. LncRNA usually competes with microRNA to regulate the expression level of downstream genes, while exosomes, as a carrier of intercellular information transfer, transmit the biological information of mother cells to target cells, and the effect of exosomes secreted by different cells on OA are different. In this review, we emphasized that different microRNA, lncRNA, and exosomes have different regulatory effects on chondrocyte proliferation and apoptosis, extracellular matrix degradation and inflammation. Besides, we classified and analyzed these molecules according to their effects on the progress of OA. Based on the analysis of the reported literature, this review reveals some pathogenesis of OA, and emphasizes that microRNA, lncRNA, and exosomes have great potential to assist early diagnosis and effective treatment of OA.